(untitled) (American Journal of Research in Humanities and Social Sciences, 2026)
This article provides a scientific analysis of the constitutional and legal foundations for ensuring human rights and freedoms in Uzbekistan, as well as the role and significance of national human rights institutions. In particular, it highlights the history of the establishment, legal status, powers, and main areas of activity of the institution of the Commissioner for Human Rights (Ombudsman) of the Oliy Majlis of the Republic of Uzbekistan. The paper also examines the practical results of the Ombudsman’s activities, mechanisms for restoring violated citizen rights, and the system for processing appeals. The article substantiates that ensuring the primacy of human rights is a key indicator of a democratic state and discusses issues of improving the activities of national institutions and aligning them with international standards. The research results have both theoretical and practical significance in developing effective mechanisms for the protection of human rights.